An Asian orchid, Eulophia graminea (Orchidaceae: Cymbidieae), naturalizes in Florida - Pemberton, Robert W. (Universidad de Costa Rica, 2008)
Eulophia graminea, a terrestrial orchid native to Asia, has naturalized in southern Florida. Orchids naturalize less often than other flowering plants or ferns, but E. graminea has also recently become naturalized in Australia. Plants were found growing in five neighborhoods in Miami-Dade County, spanning 35 km from the most northern to the most southern site, and growing only in woodchip mulch at four of the sites. Plants at four sites bore flowers, and fruit were observed at two sites. Hand pollination treatments determined that the flowers are self compatible but fewer fruit were set in selfed flowers (4/10) than in out-crossed flowers (10/10). No fruit set occurred in plants isolated from pollinators, indicating that E. graminea is not autogamous. Pollinia removal was not detected at one site, but was 24.3 % at the other site evaluated for reproductive success. A total of 26 and 92 fruit were found at these two sites, where an average of 6.5 and 3.4 fruit were produced per plant. These fruits ripened and dehisced rapidly; some dehiscing while their inflorescences still bore open flowers. Fruit set averaged 9.2 and 4.5 % at the two sites. No floral visitors were seen during limited (6.5 hr duration) timed watches of flowers. Individual flowers are open an average 11 days, and the inflorescences may bear flowers for at least one month. How E. graminea entered Florida is unknown, but capsules, bulbs and plantlets in flasks are available for sale and/or trade via the internet from Thailand and other places outside the U.S. The occurrence of the orchid at 900-1000 m elevation its native Sikkim (27-28oN) and in Kashmir (above 32oN), suggest that it can live well north of current area of naturalization in southern Florida, which is at sea level and 26oN latitude.